Determining the recharge sources and circulation depth of thermal waters in Xianyang geothermal field in Guanzhong Basin: The controlling role of Weibei Fault. (September 2017) - Luo, Lu; Pang, Zhonghe; Liu, Jinxia; Hu, Shengbiao; Rao, Song; Li, Yiman; Lu, Lianghua
Highlights: Proved that the geothermal waters in Xianyang are recharged from precipitation of Qinling Mountain and geothermal fluids are of shallow crustal origin by using hydrochemistry and fluid isotope methods. Found and explained the "oxygen isotope shift" phenomenon in Xianyang geothermal waters. Established a conceptual model of Xianyang geothermal field firstly. Abstract: Xianyang geothermal field located in Guanzhong Basin is being used for space heating so it is necessary to understand the recharge and circulation of the thermal water in order to ensure sustainability of production. Weibei Fault that cuts through the field is believed to play a key role in the formation of the geothermal field and is investigated in this study. Isotope results indicate that the geothermal water in Xianyang geothermal field is recharged mainly from Qinling Mountain on the southern side of the Guanzhong Basin. Geothermal water in the northern side of Weibei Fault is more matured than that in the southern side in terms of chemistry. The deeper reservoir exhibits a stronger oxygen shift. The maximum reservoir temperature estimated for the south and north sectors are markedly different: 134 °C and 106 °C, respectively. Accordingly, the average thermal gradients based on well logging in the south range from 2.2 to 3.5 °C/100 m, and in the north range from 3.2 to 3.3 °C/100 m. The circulation depths of geothermal water in the south and north of the Weibei Fault are calculated to be 2352–4120 m and 2444–2780 m, respectively. Using geothermometry, in combination with geothermal gradients, greatly improves depth estimation of geothermal reservoirs.